SEX AND WOMEN IN THE SCRIPT OF THE STORY OF SHEIKH MARDAN ACCORDING TO BUGESE AND MAKASSARESE VERSIONS - Mustari, Mustari; Zaini, Hisyam (UI Scholars Hub, 2023)
Sex and women are always interesting to talk about due to their mysterious nature. Discussion on the topic will get more interesting when it is related to illegal practice done by spiritual figures who look for the position of insan kamil or perfect human being. Such kind of depiction is found in popular stories that live among Bugis and Makassar people, known as Paupaunna Séheq Maradang in Bugis tradition, and Paupaunna Séhu Maradang in Makassar tradition. The script was originally transformed from Javanese to Malay and spread to Nusantara languages including, Bugese and Makassarese. Both versions of this text have been used as a tool of da'wah because the core of this story is the spiritual journey of a prince named Sheikh Mardan in perfecting his religious knowledge. Inhis spiritual journey, he always met a woman (the king's daughter) and married her. There are some differences between the Bugese language version and the Makassarese language version. That difference will be revealed in this study and followed by explanation of their differences. To sharpen the analysis, comparative literary theory is used. The output of this study is controversy related to illegal sex has been addressed differently by people through both versions. The Makassarese version allows the narrative of free sex performed by the main character with the two princesses he first met, while the Bugese language version seeks a way out by inner marriage.